2017
DOI: 10.3346/jkms.2017.32.4.688
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Clinical Characteristics of Rapid Response System Activation in Patients Admitted to Medical or Surgical Services

Abstract: Variability in rapid response system (RRS) characteristics based on the admitted wards is unknown. We aimed to compare differences in the clinical characteristics of RRS activation between patients admitted to medical versus surgical services. We reviewed patients admitted to the hospital who were detected by the RRS from October 2012 to February 2014 at a tertiary care academic hospital. We compared the triggers for RRS activation, interventions performed, and outcomes of the 2 patient groups. The RRS was act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…As care factors, medical patients tended to have worse outcomes than did surgical patients. This finding was similar to previous findings (Lee et al, 2017 showing that patients with interventions by rapid response teams had higher mortality (Lee et al, 2017;Tirkkonen, Tamminen, & Skrifvars, 2017). These findings may indicate that appropriate, timely management at ICU/HDB and operating room, without escalated care or rapid response team activation, resulted in better outcome.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As care factors, medical patients tended to have worse outcomes than did surgical patients. This finding was similar to previous findings (Lee et al, 2017 showing that patients with interventions by rapid response teams had higher mortality (Lee et al, 2017;Tirkkonen, Tamminen, & Skrifvars, 2017). These findings may indicate that appropriate, timely management at ICU/HDB and operating room, without escalated care or rapid response team activation, resulted in better outcome.…”
Section: Discussionsupporting
confidence: 90%
“…In Korea, there are presently no nationally recommended early warning scoring systems, or even guidelines regarding the implementation of a rapid response system. Korean hospitals have operated rapid response systems using locally developed multiple clinical parameters (Kwak et al, 2014;Lee et al, 2017). Prior research has shown that aggregate weighted early warning scoring systems were better at predicting clinical deterioration than early warning scoring systems based on single or multiple parameters (Churpek, Yuen, & Edelson, 2013;McNeill & Bryden, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, new models with additional factors such as lactic acid or d-dimer levels, which have not been included in traditional EWS models, have been developed and validated to improve accuracy according to targeted patient groups [ 8 , 9 ]. There is also a need for tailored EWS models to ensure practical usefulness in the respiratory wards [ 10 ].…”
Section: Introductionmentioning
confidence: 99%